Mixed-mode I + III interlaminar fracture of carbon/epoxy laminates - Pereira, A. B.
A new test was developed for measuring the mixed mode I + III interlaminar fracture toughness. The specimen adopted was an 8-point bending plate (8PBP) with a cross-ply lay-up and a mid-thickness edge pre-delamination at the standard 0/0 interface. Finite element analyses (FEA) showed that a wide range of mode mix ratios can be achieved by varying the load point displacements imposed. However, the need of FEA based experimental data reduction and of a relatively complicated fixture are important drawbacks of test developed. Nevertheless, results for carbon/epoxy laminates showed a realistic evolution of initiation Gc values with the GIII/G mode mix ratio.